2013
DOI: 10.1016/j.fct.2013.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of organic acids in electron beam irradiated chestnuts (Castanea sativa Mill.): Effects of radiation dose and storage time

Abstract: Since 2010, methyl bromide, a widely used fumigant was banned from the European Union under the Montreal Protocol guidelines, due to its deleterious effects on health and risk to the environment. Since then, many alternatives for chestnut conservation have been studied (hot water dip treatment being the most common), among them, electron beam irradiation has been proposed as being a safe, clean and cheap alternative.Herein, the effects of this radiation at different doses up to 6 kGy and over storage up to 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
22
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 32 publications
7
22
1
1
Order By: Relevance
“…Thus, irradiation does not cause great changes in the total or individual content of organic acids (Carocho et al . ). Other researchers have reported that irradiation increased the quinic acid content (Kim and Yook ).…”
Section: Resultsmentioning
confidence: 97%
“…Thus, irradiation does not cause great changes in the total or individual content of organic acids (Carocho et al . ). Other researchers have reported that irradiation increased the quinic acid content (Kim and Yook ).…”
Section: Resultsmentioning
confidence: 97%
“…The organic acids extraction was performed according to the method described by Carocho et al [20] with some modifications, namely the addition of internal standard and the application of a sequential extraction. In more detail, samples (500 mg, in duplicate) were mixed with 5 mL of meta-phosphoric acid (3%, w/v) and 150 µL of gallic acid, as internal standard (1 mg/mL), for 30 min in a vortex.…”
Section: Organic Acids Analysismentioning
confidence: 99%
“…The organic acid extraction was performed with meta-phosphoric acid (3%, w/v), according to the method described by Carocho et al [27] , with some modifications in what regards the addition of an internal standard and the application of a sequential extraction. In more detail, samples (500 mg, in duplicate) were mixed with 150 µL of gallic acid solution (1 mg mL…”
Section: Organic Acid Extractionmentioning
confidence: 99%